Accelerating action towards net positive agriculture and food systems - Lomax, James; Pesce, Federica; Estrada Carmona, Natalia; Thallam, Vijay Kumar (2023)
Sustainable food systems are essential to providing healthy and nutritious food while enhancing livelihoods and climate resilience for people and the planet. While there are many forms of agriculture that support food security, healthy diets, economic prosperity and the environment; unsustainable agricultural practices are also a key contributor to the triple planetary crisis of biodiversity loss, climate change, and pollution and waste. Responding to these challenges requires taking a systems-based approach that addresses these complexities in a holistic and sustainable manner. Building on the outcomes of the 2021 UN Food Systems Summit, which launched bold new actions for progress on all 17 SDGs through the development of national food systems pathways; in this paper we consider agricultural systems as an integral part of food systems and evaluate their contribution to sustainable development outcomes - specifically those that are biodiversity-friendly, climate-resilient, pollution-free and human-centered.